Simultaneous Bilateral Total hip Arthroplasty in Patients With Juvenile Idiopathic Arthritis via Direct Anterior Approach: Long-Term Outcomes - Mohammadreza Razzaghof, MD, MPH; Mohammad Vahedian Ardakani, MD; Mohammad Poursalehian, MD; Seyyed Hossein Shafiei, MD; Mahlisha Kazemi, MD; Seyed Mohammad Javad Mortazavi, MD (Arthroplasty Today)
Background: Juvenile idiopathic arthritis (JIA) often results in significant bilateral hip damage, necessitating total hip arthroplasty (THA). Simultaneous bilateral THA offers potential advantages, particularly when executed via the Direct Anterior Approach (DAA). This study aims to assess the functional, radiological, and patient-reported outcomes, along with the complications of bilateral uncemented THA performed via DAA in patients with JIA. Methods: A retrospective review of 39 patients with JIA who underwent bilateral THA via DAA from January 2006-January 2015 was conducted. Inclusion and exclusion criteria were defined, focusing on a minimum of 7 years of post-THA follow-up. Functional outcomes were assessed using the Harris Hip Score. Results: Data were available for 33 patients (66 hips). The mean age at surgery was 21.3 years, and the average follow-up was 11.3 years. All patients reported severe bilateral hip pain presurgery, which was alleviated post-THA. The mean preoperative Harris Hip Score improved from 49.6-79.7 postoperatively. Complications included 3 calcar cracks, 2 greater trochanter fractures, and 1 superficial wound dehiscence. No instances of dislocation, postoperative periprosthetic fracture, or any revision surgery were recorded. Conclusions: Simultaneous bilateral THA using DAA is an effective and safe surgical approach for patients with JIA with bilateral end-stage hip involvement, providing notable improvements in functional and radiological outcomes while maintaining a favorable complication profile. Level of evidence: IV.